Pengembangan Buku Suplemen Teks Prosedur Berbasis Ekopedagogi untuk Menumbuhkan Kesadaran Ekologis Peserta Didik SMP Kelas VII - Talan, Maria Rosalinda; Pribadi, Nirbito Hanggoro; Hano’e, Emanuel M. Y.; Nino, Septoriana Maria (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The low literacy skills of students, the lack of teachers’ role as facilitators, and environmental conditions that increasingly show an ecological crisis are the basis for the design of this research and the development of this supplementary book. The purpose of this study is to describe the process and results of developing an eco-pedagogy-based procedural text supplementary book and to describe the ecological awareness of students. The development of the supplementary book used the Four D Model (4D). The data on the development process of the supplementary book consists of descriptions of activities starting from the definition stage, the design stage, and the development stage. The data on the quality of the supplementary book consists of data on the level of validity, practicality, and effectiveness of the supplementary book. The data on the ecological awareness of students consists of the level of ecological awareness. The technique used in collecting data on the development process of the supplementary book is the observation technique. The data collection techniques used to obtain data on the quality of the supplementary book were questionnaires, observation, and tests. Meanwhile, the technique used to obtain data on the ecological awareness of students was questionnaires. The results showed that the supplementary book developed was of high quality and could be applied in junior high school Indonesian language learning. In addition, the results also showthat students have ecological awareness after participating in ecopedagogical-based procedural text learning. Thus, the results of the development of this supplementary book greatly help students to have holistic competencies, namely to acquire positive attitudes reflected in ecological awareness, as well as to acquire knowledge and skills evident from the learning outcomes of students.